Genomic and Transcriptomic Analysis of Growth-Supporting Dehalogenation of Chlorinated Methanes in Methylobacterium - Chaignaud, Pauline; Maucourt, Bruno; Weiman, Marion; Alberti, Adriana; Kolb, Steffen; Cruveiller, Stéphane; Vuilleumier, Stéphane; Bringel, Françoise (Frontiers in Microbiology, 2017)
Bacterial adaptation to growth with toxic halogenated chemicals was explored in the context of methylotrophic metabolism of Methylobacterium extorquens, by comparing strains CM4 and DM4, which show robust growth with chloromethane and dichloromethane, respectively. Dehalogenation of chlorinated methanes initiates growth-supporting degradation, with intracellular release of protons and chloride ions in both cases. The core, variable and strain-specific genomes of strains CM4 and DM4 were defined by comparison with genomes of non-dechlorinating strains. In terms of gene content, adaptation towards dehalogenation was limited, strains CM4 and DM4 sharing between 75 and 85% of their genome with other strains of M. extorquens. Transcript abundance in cultures of strain CM4 grown with chloromethane and of strain DM4 grown with dichloromethane was compared to growth with methanol as a reference C1 growth substrate. Previously identified strain-specific dehalogenase-encoding genes were the most transcribed with chlorinated methanes, alongside other genes encoded by genomic islands (GEIs) and plasmids involved in growth with chlorinated compounds as carbon and energy source. None of the 163 genes shared by the strains CM4 and DM4 but not by other strains of M. extorquens showed higher transcript abundance in cells grown with chlorinated methanes. Among the several thousand genes of M. extorquens core genome, 12 genes were only differentially abundant in either strain CM4 or strain DM4. Of those, 2 genes of known function were detected, for the membrane-bound proton translocating pyrophosphatase HppA and the housekeeping molecular chaperone protein DegP. This suggested that the adaptive response common to chloromethane and dichloromethane was limited at the transcriptional level, but involved aspects of the general stress response as well as of a dehalogenation-specific response to intracellular hydrochloric acid production. Other core genes only differentially abundant in either strain CM4 or strain DM4 implied 13 and 58 genes, respectively. Taken together, the obtained results suggest different transcriptional responses of chloromethane- and dichloromethane-degrading M. extorquens strains to dehalogenative metabolism, and substrate- and pathway-specific modes of growth optimization with chlorinated methanes.